Acute hamstring injury in football players: Association between anatomical location and extent of injury—A large single-center MRI report. Issue 4 (April 2016) - Crema, Michel D.; Guermazi, Ali; Tol, Johannes L.; Niu, Jingbo; Hamilton, Bruce; Roemer, Frank W.
Abstract: Objectives : To describe in detail the anatomic distribution of acute hamstring injuries in football players, and to assess the relationship between location and extent of edema and tears, all based on findings from MRI. Design : Retrospective observational study. Methods : We included 275 consecutive male football players who had sustained acute hamstring injuries and had positive findings on MRI. For each subject, lesions were recorded at specific locations of the hamstring muscles, which were divided into proximal or distal: free tendon, myotendinous junction, muscle belly, and myofascial junction locations. For each lesion, we assessed the largest cross-sectional area of edema and/or tears. We calculated the prevalence of injuries by location. The relationships between locations and extent of edema and tears were assessed using a one-sample t -test, with significance set at p < 0.05. Results : The long head of biceps femoris (LHBF) was most commonly affected (56.5%). Overall, injuries were most common in the myotendinous junction and in proximal locations. The proximal myotendinous junction was associated with a greater extent of edema in the LHBF and semitendinosus (ST) muscles ( p < 0.05). Proximal locations in the LHBF had larger edema than distal locations ( p < 0.05). Distal locations in the ST muscle had larger tears than proximal locations ( p < 0.05). Conclusions : The proximal myotendinous junction (LHBF and ST muscles) and proximal locations (LHBF muscle) are more commonly affected and are associated with a greater extent of edema in acute hamstring muscle injury. Distal locations (ST muscle), however, seem to be more commonly associated with larger tears.